A comparative analysis of deck log records of merchant ships. Issue 1 (2nd January 2021) - Turna, İdris and Öztürk, Orkun Burak
ABSTRACT: In many studies involving historical and climatological subjects, it is known that deck log records are used as a major source. The deck log books have also appeared as one of the key sources of marine accident investigations. Recently, many international conventions impose obligations for different types of records. It is seen that record requirements do not come from a single written source. As a result, different applications and deficiencies arise. Keeping incomplete records is reflected as a deficiency in PSC inspection reports, and even in some cases, it leads to the detention of ships. The aim of this study is to collect the deck-log recording requirements from different sources, classify them under main titles and compare their distribution by a quantitative approach. Recording requirements were obtained from SOLAS, MARPOL, ILO, MLC, COLREG, P&I, and Flag states, a total of 135 record examples were collected for different stages of ship operation. One unanticipated finding was that SOLAS Chapter 5 and ICS Bridge Procedures Guide are not a sufficient guide for up-to-date deck log recording requirements. The study provides a systematic analysis of recording standards, unlike previous studies that use deck recordings only as data sources.